Biological effects of trans, trans-farnesol in Leishmania amazonensis - Pinheiro, Liliane Sena; Andrade-Neto, Valter Viana; Mantuano-Barradas, Marcio; Pereira, Elisa Cavalcante; Barbosa, Rodrigo Cesar Fernandes; de Oliveira, Marcia Cristina Campos; Menna-Barreto, Rubem Figueiredo Sadok; Cunha-Júnior, Edézio Ferreira; Torres-Santos, Eduardo Caio (Frontiers in Cellular and Infection Microbiology, 2023)
Farnesol is produced by an alternative route from farnesyl pyrophosphate, an intermediate of the sterols biosynthetic pathway. The farnesol molecule has three unsaturations with four possible isomers; however, the main form secreted by Candida albicans is the trans, transfarnesol (t, t-FOH). This isoprenoid regulates the virulence of different fungi species, modulating morphological transition processes. In addition, the farnesol produced by Candida albicans can influence the susceptibility or resistance of the fungus itself and, at high concentrations, leads the fungus to apoptosis. Interestingly, trypanosomatids and fungi have sterol biosynthesis machinery that differs in some steps of the mammalian pathway. So, due to an evolutionary divergence, fungi and trypanosomatids synthesize sterols with the ergostane skeleton and do not synthesize cholesterol. Based on these similarities, this work aims to evaluate the interference of farnesol on the proliferative ability of L. amazonensis and identify its presence on the lipid secretome of the parasite. Trans, trans-farnesol added exogenously interferes in the proliferation of promastigotes and inhibits the cell cycle without causing DNA fragmentation or loss of mitochondrial functionality. Subsequently, the lipid secretome was analyzed. While t, t-farnesol was not detected in the culture supernatant, other products derived from the same precursor, farnesyl pyrophosphate, namely α-farnesene and β-farnesene, were detected starting on the fourth day of culture and continued to increase until the tenth day. Additionally, we identified the sequence for the farnesene synthase gene in the Leishmania genome through in silico analysis, which is the enzyme responsible for producing these isoprenoids. These findings collectively provide the first insights into the mechanism of action of farnesol on L. amazonensis and the identification of its associated isoprenoids in the parasite's lipid secretome.